A new anthracothere (Artiodactyla) from the early Oligocene, Fayum, Egypt, and the mystery of African 'Rhagatherium' solved. (15th June 2016) - Sileem, Afifi H.; Sallam, Hesham M.; Hewaidy, Abdel Galil A.; Miller, Ellen R.; Gunnell, Gregg F.
Abstract: Recent work on new anthracothere (Mammalia, Artiodactyla) specimens from the Jebel Qatrani Formation, early Oligocene, Fayum, Egypt, has revealed the presence of a new genus. Nabotherium new genus is described on the basis of a partial skull, several mandibular and maxillary specimens, and isolated teeth. The new genus exhibits a distinctive combination of features not seen in other Paleogene anthracotheres. The most noticeable characteristics of the new genus include the presence of large and well-developed upper and lower canines, caniniform third incisors, the presence of only a short diastema between the canine and first premolar, and broad, bunodont cheek teeth. This is in contrast to other contemporary anthracotheres, including other forms from the Fayum, which show a spatulate third incisor, a reduced canine, a much longer canine-premolar diastema, and more narrow, bunoselenodont cheek teeth. The presence of a relatively short rostrum with closely packed incisors, low-crowned and simple premolars, and low-crowned, bunodont molars indicates that members of the new genus would have been more efficient at crushing foods than slicing vegetation, and suggests a more varied herbivorous and frugivorous diet than was favored by other, more bunoselenodont Fayum anthracotheres.